Amy Krois-Lindner, Matt Firth and Translegal: Introduction to International Legal English - Barbora Chovancová (Časopis pro Právní Vědu a Praxi, 2011)
Recenze publikace - Amy Krois-Lindner, Matt Firth and Translegal: Introduction to International Legal English Cambridge University Press, ISBN 978-0-521-71899-8, 2008, 160 s.